(untitled) (Al-Aasar, 2025)
Imam Ahmad Raza Khan Barelvi (1856–1921) occupies a distinguished position among the great Muslim scholars of the Indian subcontinent due to his vast knowledge, intellectual depth, and remarkable research contributions. This research paper examines his scholarly status as a researcher (Muhaqqiq) by analyzing his methodology, principles of research, and services in various Islamic sciences. Imam Ahmad Raza emphasized strict adherence to primary sources, critical evaluation of texts, and comparative study of manuscripts before deriving conclusions. His renowned compilation Fatawa Razvia reflects a highly systematic, evidence-based, and principled research approach grounded in the Qur’an, Hadith, consensus (Ijma‘), and classical jurisprudence. Similarly, his translation of the Qur’an, Kanz al-Iman, demonstrates linguistic precision, theological soundness, and deep understanding of Qur’anic sciences. The study highlights that Imam Ahmad Raza’s research methodology was not limited to jurisprudence but extended to Hadith, Tafsir, theology, and refutation of false ideologies. His scholarly legacy proves that he was a comprehensive and visionary researcher whose principles of research remain highly relevant for contemporary Islamic scholarship.